Analisis Dampak Ekonomi Pelaksanaan Jalan Simpang Rukis - Tanjung Kemuning Provinsi Bengkulu - Azuwandri Azuwandri (COSTING : Journal of Economic, Business and Accounting, 2019)
Public transportation is transportation that is needed by most urban communities, a city cannot survive without public transportation. The main objective of this study is to determine the reduction of road user costs and financial analysis of NPV (Net Present Value) and BCR (Benefit Cost Ratio). The research method used is descriptive which is used to analyze the impact of time and cost savings, the method used is a descriptive statistical method, NPV and BCR Financial Impact Testing and investment feasibility sensitivity analysis. The results showed the cost efficiency of road users was Rp. 600,001.24 and increase travel speed to 50 km / hour. Vehicle Operating Costs (BOK) consist of fixed costs and operational cost components. Efficiency of expansion of vehicle operations to Rp. 1,921,187. From the financial analysis the implementation path of Simpang Rukis - Tanjung Kemuning is economically feasible. This is the result of a performance with NPV of Rp. 1,921,187, -> 0 and BCR 1.18> 1. Sensitivity analysis is shown when costs increase by 15%, NPV is Rp. 1,921,187 and BCR decreased to 1.03. When the benefits decrease by 15%, the NPV drops to Rp. 1,306,921,187 and BCR up to 1,004. When costs increase by 15% and benefits decrease by 15%, the NPV drops to Rp. 1,306,921,187 and BCR to 0.87 and the road is economically unfeasible. Conclusion, with the construction and maintenance of roads and bridges at Simpang Rukis - Tanjung Kemuning, it is hoped that the pace of transportation is efficient and economical so that it can accelerate the economy of Bengkulu province, especially the people of Simpang Rukis - Tanjung Kemuning. Keywords: Economic Feasibility, NPV, BCR, Sensitivity Analysis